Conte-moi Pompéi - Barbet, Alix (B@lades, 2021)
"Tell me about Pompeii". Is it a story, a novel, a documentary, an art book? No, but a book of initiation in the form of dialogues like the philosophers of antiquity did, a b@lade in this city frozen by a terrible volcanic eruption. Children ask questions about Pompeii and the exchanges are lively and direct. The archaeologist Alix Barbet, honorary research director at the CNRS, who has been visiting Pompeii and its region for fifty years, leads the debate. This book was published by Ausonius; now it is available in a new open format, visible to the greatest number of people, thus offering a new reading experience.